Error Analysis Students’ Ability in Using Regular and Irregular Verb at the Second Grade of SMP Satria Dharma Perbaungan - Widya Santiwi Br Simanjuntak, Yusnita Nasution (Continuous Education: Journal of Science and Research, 2023)
This research aims to analyze student errors made by second grade students of SMP Satria Dharma Perbaungan in using regular and irregular verbs. This research aims to obtain the types of errors in identifying regular and irregular verbs in the past form and to find out the causes of why students make mistakes. This type of research is research with qualitative methods. This research was conducted by following error analysis procedures, starting with sample selection, identification, elaboration, explanation and assessment of errors. The data sources in this research were 10 students from the second grade of SMP Satria Dharma Perbaungan. The research data was obtained by doing observations, giving questionnaires and giving tests to students. From the error analysis process, it was found that students made three types of errors, namely ommission, addition, and misformation. The results of omission errors were 23.34%, addition errors were 26.66% and the most errors occurred at 50% misformation errors. According to the theory of Ellis and Barkhuizen, students' errors are caused by interlingual transfer and intralingual transfer.